2015
DOI: 10.13187/ejced.2015.14.232
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Expression of Senior High School Age Students in Physical Education Classes

Abstract: The main purpose of the present study is to reveal the peculiarities of social skills expression of senior high school age students in physical education classes. The independent random sample consisted of 244 (15 -16 years old) students and 258 (17 -18 years old) students, of which there were 224 boys and 278 girls. L. Bulotaitė and V. Gudžinskienė communication skills survey questionnaire, Tromsø social intelligence questionnaire and I. Yusupov's empathy diagnostic method were employed. It was found that 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
6
0
4
Order By: Relevance
“…Siguiendo la tabla 2, podemos ver cómo para los alumnos, la EE como fin supone el 52% de los artículos recogidos, desglosando a su vez esta categoría en programas de EE, los cuales parten de las propias sesiones de EF (Simonton, Gran y Solmon, 2017;Garn, Simonton, Dasingert y Simonton, 2017;Akelaitis, 2015), del juego motriz (Miralles, Filella, y Lavega, 2017;Caballero et al 2016;Duran, Lavega, Salas, Tamarit e Inverno, 2015), de la aplicación de la condición física (Mujica, Orellana, Aránguiz y González, 2016) y de la autopercepción (Madrona y López, 2016). Además, se encuentran recogidas Tabla 1 Análisis de los artículos seleccionados en la relación de la Educación Emocional y la Educación Física.…”
Section: Resultsunclassified
“…Siguiendo la tabla 2, podemos ver cómo para los alumnos, la EE como fin supone el 52% de los artículos recogidos, desglosando a su vez esta categoría en programas de EE, los cuales parten de las propias sesiones de EF (Simonton, Gran y Solmon, 2017;Garn, Simonton, Dasingert y Simonton, 2017;Akelaitis, 2015), del juego motriz (Miralles, Filella, y Lavega, 2017;Caballero et al 2016;Duran, Lavega, Salas, Tamarit e Inverno, 2015), de la aplicación de la condición física (Mujica, Orellana, Aránguiz y González, 2016) y de la autopercepción (Madrona y López, 2016). Además, se encuentran recogidas Tabla 1 Análisis de los artículos seleccionados en la relación de la Educación Emocional y la Educación Física.…”
Section: Resultsunclassified
“…cooperation) that lead to desired social outcomes (Riggio, Riggio, Salinas, & Cole 2003). Students with higher social skills tend to perform better in school (Zsolnai & Kasik 2014), have better quality relationships, resolve conflict in more constructive ways, and engage less frequently in unhealthy behaviours (Akelaitis, 2015;Gresham, 2016;Gumpel, 2007). Social skills also tend to enhance productivity and career success (Riggio et al, 2003).…”
Section: Aspects Of Social Skillsmentioning
confidence: 99%
“…One of the reasons this study is needed is because the available data in the field of gender differences in social skills and personal responsibility are somewhat contradictory. Some studies have found that the teachers' and parents' ratings of social skills were higher for boys than for girls (Nourani, 1998) although other research on social skills and personal responsibility indicates that girls typically have higher social skills and personal responsibility than boys (Akelaitis, 2015;Christodoulides, Derri, Tsivitanidou, & Kioumourtzoglou, 2012). These research results show the need for further investigation.…”
Section: Gender Differences In Social Skills and Personal Responsibilitymentioning
confidence: 99%
See 2 more Smart Citations